(untitled) (Revista Apotheke, 2024)
This manuscript is an excerpt from a master’s degree research, crossed by the philosophies of difference, which focuses on a re-education facility, driven by the question: what can aesthetic experiences do in a space for re-education of children and young people? The study carried out in an institutional shelter in an inland municipality in Rio Grande do Sul, Brazil, proposes aesthetic experiences with the aim of creating circumstances (Deligny, 2018a) amidst art and children and young people who live in re-educational facilities. Research with art (Mossi; Oliveira, 2018) is crossed by the continuous construction of visual and/or textual diaries (Oliveira, 2012) and calls upon authors such as Deligny (2018a, 2018b), Foucault (2014) and Deleuze (1988-1989, 1992, 2006) to produce theoretical contagions. The focus is on inventing new paces to inhabit re-education facilities, paces open to the “useless”, in which there is no intention of producing or teaching anything to children at any age, assuming “infanciar” (Kohan; Fernandes, 2023) as a condition to create circumstances.